Perspectives of Virtual reality (VR) adoption in Logistics/Supply Chain Management - Amer, Ahmed; Jirsák, Petr; Martínez, Felipe; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
In a rapidly changing field, the potentials of 'Virtual Reality' (VR) and 'Augmented Reality' (AR) technologies are transformational enough to redefine conventional operational processes, training methodologies, and make sure that the resultant overall operational efficiencies are improved. This thesis tries to explore the current landscape of adoption of VR and AR within the logistics sector, extract the barriers that exist against their successful integration, and suggest strategic plans in order to overcome the same. This study has been able to unearth practical benefits and persisting skepticism about technologies by qualitatively using semi-structured interviews with industry professionals. In fact, the results indicated that the potential of VR and AR technologies in accuracy, efficiency, and safety enhancement of logistics operations is very promising, but the actualization of those potentials is restrained by high implementation costs, technological complexities, and the absence of robust integration frameworks with existing systems. It thus borrows from theoretical models such as the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT) to explain these phenomena and proffer custom-tailored adoption strategies that cut across the organizational and technological barriers. It offers a complete outline of VR and AR applications synthesizing empirical insights with theoretical perspectives to make a contribution in the scholarly discussion of digital innovation within logistics, relevant for academia and practice, outlining a roadmap for future research and its practical implementations in the industry.
Vedoucí práce: Petr Jirsák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses